2020
DOI: 10.1177/1367493520971426
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurse retention within children’s palliative care

Abstract: Retention of staff presents major challenges within children’s palliative care; this has substantial implications for children, families and the nursing workforce. To address this, a programme was undertaken that provided pathways of professional development for senior nurses working in this field. This study reports the views of nurses completing this programme, the overall project manager (PM) and the day-to-day programme lead (PL) as well as factors that influence nurse retention within children’s palliativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This at times generated feelings that they were providing impersonal or inadequate care. The findings from a number of studies likewise revealed demanding workloads with implications such as stress and fatigue for healthcare professionals (McCloskey & Taggart, 2010; Quinn & Bailey, 2011; Whiting et al, 2020). However, the healthcare professionals in the present study seemed to ‘find’ time, knowing perhaps the way to ‘create’ time was by being fully engaged with each family in the moments that were available.…”
Section: Discussionmentioning
confidence: 98%
“…This at times generated feelings that they were providing impersonal or inadequate care. The findings from a number of studies likewise revealed demanding workloads with implications such as stress and fatigue for healthcare professionals (McCloskey & Taggart, 2010; Quinn & Bailey, 2011; Whiting et al, 2020). However, the healthcare professionals in the present study seemed to ‘find’ time, knowing perhaps the way to ‘create’ time was by being fully engaged with each family in the moments that were available.…”
Section: Discussionmentioning
confidence: 98%
“…Organizations must be attentive to this (Rawlings et al, 2020b), and offer staff the opportunity and time for self-care (Beaune et al, 2018) and team building (Dryden-Palmer et al, 2018). Strategies that can help to retain staff working in these areas include formalized support mechanisms, such as Employee Assistance Programs (EAPs) and clinical supervision, as well as education and professional development (Whiting et al, 2020). Some learners also reported feeling helpless in view of imminent death (Grimston et al, 2018), with challenges noted in talking to the child and their family about dying, and in prognosticating.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly this included the well-reported staff shortages and high attrition in the professions [as reported above, within aim (a)], which could have knock on implications. For example, Lone working (N, 99,118,119 Poor relationships with colleagues/incivility/ bullying 9,25,30,34,75,83,89,90,96,110,123 Fear of assault/abuse from public/patients (P, 124 but also N and M in some settings e.g. emergency nurses, 23 secure forensic 25,111 ) Challenging relationships with patients, public, clients 23,80,100,105,106,111,124,125 Not feeling able to speak out 9,83,90,94,114 continued one nursing paper focused on newly qualified nurses 73 highlighted that this can mean regularly working with temporary staff (bank or agency staff) and/or being moved to other units (impacting teamwork and collegiality as well as knowledge of the systems and patients), and that such shortages can often mean being the only registered nurse on a shift, leading to feeling "vulnerable, and their units unsafe" 73 (p. 3).…”
Section: Demandsmentioning
confidence: 99%
“…Lack of support related mostly to poor support from leadership/managers and organisational-level support, with one paramedic paper stating that it was a lack of confidence in support from employers that led paramedics to self-refer to their regulator. 114 However, one nursing paper highlighted the lack of support for leaders (senior nurses): '(it is) quite lonely at the top when you have no one to speak to' 110 (p. 8), and a paramedic paper described the culture as sometimes being unsupportive if a colleague was struggling, referring to the military background of the profession and that there was consequently a very low tolerance for low standards amongst peers. 115 In one midwifery paper, midwives described feeling invisible and not being acknowledged, 83 and another referred to the harsh mentorship they had received and lack of kindness from managers/mentors, 116 with a third describing how midwives felt 'scrutinised rather than supported by management' 89 (p. e553).…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation